2013
DOI: 10.1038/bcj.2013.42
|View full text |Cite
|
Sign up to set email alerts
|

PKR negatively regulates leukemia progression in association with PP2A activation, Bcl-2 inhibition and increased apoptosis

Abstract: Reduced expression and activity of the proapoptotic, double-stranded RNA-dependent protein kinase, PKR (protein kinase R) is observed in breast, lung and various leukemias, suggesting that loss of PKR potentiates transformation. Now we report that decreased PKR activity inhibits chemotherapy-induced apoptosis of leukemia cells both in vitro and in vivo. Inhibition of PKR expression or activity reduces protein phosphatase 2A (PP2A) activity, a B-cell lymphoma 2 (Bcl-2) phosphatase, resulting in enhanced Bcl-2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…11 Generation of cell lines expressing short hairpin RNA (shRNA) is described in supplemental Methods. PKRI compound, okadaic acid (OA), and antiphospho(serine 1981)-ataxia-telangiectasia mutated (p-ATM) antibody, clone 10H11.E12, were purchased from EMD Millipore (Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…11 Generation of cell lines expressing short hairpin RNA (shRNA) is described in supplemental Methods. PKRI compound, okadaic acid (OA), and antiphospho(serine 1981)-ataxia-telangiectasia mutated (p-ATM) antibody, clone 10H11.E12, were purchased from EMD Millipore (Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Sodium dodecyl sulfate-polyacrylamide gel electrophoresis and immunoblotting was performed as previously described. 11 For IP, 500 mg of protein lysate was precleared with nonspecific mouse immunoglobulin (Ig)G and protein G, then incubated overnight with the indicated antibody (1:100 dilution) and protein G agarose (Life Technologies, Grand Island, NY) at 4°C. Agaroseconjugated complexes were washed with PBS and detected by immunoblotting as described.…”
Section: Nuclear Fractionation Immunoblotting and Immunoprecipitatimentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it has been reported that PKR is suppressed or inactivated in some malignancies, and increased PKR expression has been shown to correlate with better prognosis in head and neck cancer, melanoma, and lung and colon cancer (71)(72)(73)(74)(75)(76). Furthermore, some evidence shows that PKR may act as a tumor suppressor in leukemia (77) and could play an important role in hematologic disorders (78,79).…”
Section: Pkr Plays a Dual Role In Cancermentioning
confidence: 99%